Kekasaran Permukaan Proses Pembubutan Dry Dan Wet Process Baja ST 90 Dengan Insert Carbide - Dimas Adi Perwira; Henry Widya Prasetya; Affan Nur Roja Jendra Prakoso (Virtual of Mechanical Engineering Article, 2022)
Abstract Railway components especially for parts of that often occur friction and resist when there is a pulling or pushing must have a low roughness to reduce the occurrence wear caused by frictioning and as an indicator good or bad quality of a product. The purpose of this study is to know the effect of roughness level of cutting parameter variation, wet process manufacturing method variation, dry process and nose radius variations of chisel lathe 0.4, 0.8 in the ST 90 The method used in this study is experimental. The independent variables in this study were variations in cutting parameters, nose radius of the tool, and working methods. In cutting parameters, spindle rotational speed (540 Rpm, 800 Rpm, 1500 Rpm), feed speed (0.226 mm/revolution), depth of cut (2 mm) and for nose radius using 0.4 mm and 0.8 mm, there are also variations in wet working methods. process and dry process. After testing is carried out, it shows that on the ST 90 with the wet process working method and nose radius 0.8 turning variation with spindle rotation speed of 1500 Rpm, depth of cut 2 mm, feed speed 0.226 mm/rev has a roughness value of 2.625 µm. Meanwhile, for the highest level of roughness, using the dry process method and chisel nose radius 0.4 with a turning speed of 540 Rpm, a cutting depth of 2 mm, a feed speed of 0.226 mm/rev having a roughness value of 9.223 µm. Keyword: Insert w-series, Wet process, Dry process, Surface roughness.